Africa energy future: Alternative scenarios and their implications for sustainable development strategies. (July 2017) - Ouedraogo, Nadia S.
Abstract: The long-term forecasting of energy supply and demand is of prime importance in Africa due to the steady increase in energy requirements, the non-availability of sufficient resources, the high dependence on fossil-fuels to meet these requirements, and the global concerns over the energy-induced environmental issues. This paper is concerned with modelling possible future paths for Africa's energy future and the related emissions. Future energy demand is forecasted based on socio-economic variables such as gross domestic product, income per capita, population, and urbanisation. The Long-range Energy Alternative Planning System (LEAP) modelling framework is employed to analyse and project energy demand and the related emissions under alternative strategies for the period of 2010–2040. Results of scenarios including business-as-usual (BAU) policies, moderate energy access and accelerate energy access policies, renewable energies promotion and energy efficiency policies and their environmental implications are provided. The study provides some policy insights and identifies synergies and trade-offs relating to the potential for energy policies to promote universal energy access, enable a transition to renewable energy, and mitigate climate change fora sustainable development. Graphical abstract: Highlights: Possible future paths for Africa's energy future and the related emissions are modelled. Scenarios using an adaptation of Schwartz's scenario approach, under LEAP are developed. Under the current energy policies, the universal access to modern energy will not be met by 2030. Policies to accelerate the changes in energy structure are required for sustainable development. Investing in Energy efficient strategies has emerged as one of the best solution.